Traditional or Distance Education: New Trends and Opportunities (Eurasian Scientific Herald, 2022)
Opportunities in the Traditional and distance learning methods, distance learning as an innovative teaching method are becoming more widespread in the modern educational space. This form of education opens up wide opportunities for students: getting education at the world's leading universities remotely, a wide range of distance learning programs, saving time and money, flexible schedule and individual study planning